Microneedle patch based on dissolving, detachable microneedle technology for improved skin quality of the periorbital region. Part 2: Clinical Evaluation. (4th September 2020) - Zvezdin, V.; Kasatkina, T.; Kasatkin, I.; Gavrilova, M.; Kazakova, O.
Abstract: Objective: Microneedle patches based on dissolving, detachable microneedle technology (Russian patent No. 2652567; US patent EFS No. 32735812; WO/2019/231360) are novel dermatological products that allow safe, painless and effective reduction of epidermal wrinkles after six procedures. The purpose of this study was two‐fold (a) to assess the safety and efficacy of microneedle patches comprising 650 microneedles containing hyaluronic and ferulic acids after 6 procedures of applying the applicator to the skin for 25 min; and (b) to correlate our previously reported ex vivo findings. Methods: The microneedle applicator contains 650 microneedles, which dissolve in 25 min of exposure. The effectiveness of microneedle applicators was confirmed by a randomized split‐phase study involving 82 subjects. Applications of microneedle patches were performed at intervals of two times per week, and the effectiveness was assessed at 6 weeks after the start of the study. Results: The results of the profilometric evaluation of skin smoothness demonstrated a significant reduction in the average roughness index by 65.32 ± 2.99% and in the mean skin waviness by 66.84 ± 1.6% compared with these indicators in the control group ( P  < 0.05). The therapeutic effect of the procedure was confirmed by an ultrasound examination that registered a 72.2 ± 5.4% and 25 ± 1.4% increase in echo‐density of the epidermis and dermis, respectively. An independent blinded skin evaluation by dermatologists revealed steady decrease in puffiness of the application area in 89.9% of patients, increased elasticity in 78.3% of the patients, and reduced severity of epidermal wrinkles in 89.9% of the patients. Conclusions: The applicator with 650 soluble microneedles on its surface containing hyaluronic and ferulic acids is considered a safe, effective and convenient way to improve the skin quality in the periorbital region after six procedures. Nevertheless, additional studies of soluble microneedles are required to fully assess the amount and distribution area of the injected hyaluronic acid and other active components, as well as to detail the mechanism of action of soluble microneedles to improve skin quality. Resumé: Objectif: Les patchs Microneedle basés sur la technologie de micro‐aiguille dissolvante et détachable (brevet russe n ° 2652567; brevet américain EFS n ° 32735812; WO / 2019/231360) sont de nouveaux produits dermatologiques qui permettent une réduction sûre, indolore et efficace des rides épidermiques après 6 procédures. Le but de cette étude était double: a) évaluer l'innocuité et l'efficacité des patchs de micro‐aiguilles comprenant 650 micro‐aiguilles contenant des acides hyaluronique et férulique après 6 procédures d'application de l'applicateur sur la peau pendant 25 minutes; et b) pour corréler nos résultats ex‐vivo précédemment rapportés. Méthodes: L'applicateur de micro‐aiguilles contient 650 micro‐aiguilles, qui se dissolvent en 25 minutes d'exposition. L'efficacité des applicateurs de micro‐aiguilles a été confirmée par une étude randomisée en hémi‐visage portant sur 82 sujets. Des applications de patchs de micro‐aiguilles ont été effectuées à des intervalles de 2 fois par semaine, et l'efficacité a été évaluée 6 semaines après le début de l'étude. Résultats: Les résultats de l'évaluation profilométrique de la douceur de la peau ont démontré une réduction significative de l'indice de rugosité moyen de 65, 32 ± 2, 99% et de l'ondulation cutanée moyenne de 66, 84 ± 1, 6% par rapport à ces indicateurs dans le groupe témoin (p <0, 05). L'effet thérapeutique de la procédure a été confirmé par un examen échographique qui a enregistré une augmentation de 72, 2 ± 5, 4% et 25 ± 1, 4% de l'écho‐densité de l'épiderme et du derme, respectivement. Une évaluation indépendante de la peau en aveugle par des dermatologues a révélé une diminution constante des poches de la zone d'application chez 89, 9% des patients, une augmentation de l'élasticité chez 78, 3% des patients et une réduction de la gravité des rides épidermiques chez 89, 9% des patients. Conclusions: L'applicateur avec 650 micro‐aiguilles solubles à sa surface contenant des acides hyaluronique et férulique est considéré comme un moyen sûr, efficace et pratique d'améliorer la qualité de la peau dans la région périorbitaire après 6 procédures. Néanmoins, des études supplémentaires sur les micro‐aiguilles solubles sont nécessaires pour évaluer pleinement la quantité et la zone de distribution de l'acide hyaluronique injecté et d'autres composants actifs, ainsi que pour détailler le mécanisme d'action des micro‐aiguilles solubles pour améliorer la qualité de la peau.